Less Expectation, Less Pain: Low Wealth Alleviates Sense of Unfairness - Pei, Guanxiong; Jin, Jia; Li, Taihao; Fang, Cheng (Frontiers in Psychology, 2021)
Objective wealth plays an important role in social interaction and economic decision making. Previous studies indicate that objective wealth of others may influence the way we participate in resources allocation. However, the effect of objective wealth on responses to fairness-related resource distribution is far from clear, as are the underlying neural processes. To address this issue, we dynamically manipulated proposers’ objective wealth and analyzed participants’ behavior as responders in a modified Ultimatum Game, during which event-related potentials were recorded. Behavioral results showed that participants were prone to reject unfair proposals although that rejection would reduce their own benefit. Importantly, participants were more likely to accept unfair offers from proposers with low objective wealth than from proposers with high objective wealth, with a drastic increase in acceptance rates of unfair offers from 32.79% to 50.59%. Further electrophysiological results showed that there was significantly enhanced FRN amplitude toward proposers with high (relative to low) objective wealth for unfair offers. Furthermore, the LFN amplitude was larger for all the conditions which are not high-fair, which might be the only option that did not elicit any ambiguity.. These findings suggest a strong role of proposers’ objective wealth in modulating responders’ behavioral and neural responses to fairness.